Pengaruh Efektivitas Metode Imla’ Terhadap Hasil Belajar Siswa Kelas VIII Mata Pelajaran Baca Tulis Al-Qur’an - Puspitasari, Ayu; umam, khoirul; syamsuddin (EL-Islam, 2025)
Abstract: Learning outcomes are a measure of a student's success as a learner, and are influenced by various factors, including the effectiveness of student learning. Teachers can use various educational methods to ensure that they use appropriate learning methods during the learning process, one of which is the Imla method. This method is also usually called the dictation method in other languages, where a teacher gives a lesson while the students write again in their respective books. The aim of the research was to analyze the learning outcomes of class VIII students before and after using the imla method in Reading and Writing Al-Qur'an lessons; to analyze how the imla method impacts the learning outcomes of class VIII students in learning to read and write the Qur'an at MTs Salafiyah Syafi'iyah Seblak Jombang; and to find out how effective the imla method is. Researchers use a quantitative approach. The type of research used is Quassi Experimental Design, and Pretest-Posttest Control Group Design. The results of this research are: 1) The learning results before learning the imla' method from 21 students for the experimental class got a minimum score of 64, a maximum score of 79 and an average score of 72.48 and a standard deviation of 5.363. Meanwhile, the learning results for the control class of 22 students got a minimum score of 53, a maximum score of 79, and an average score of 68.59 and a deviation score of 7.750. 2) The learning results after being given the imla' method learning from 21 students for the experimental class got a minimum score of 79, a maximum score of 91 and an average score of 84.86 and a standard deviation of 4.442. Meanwhile, the learning outcomes using conventional methods for the control class of 22 students got a minimum score of 66, a maximum score of 88, and an average score of 79.59 and a deviation score of 5.360. 3) There is an influence of the effectiveness of the imla' method on the learning outcomes of class VIII students in the Al-Qur'an Reading and Writing subject at MTs Salafiyah Syafi'iyah Seblak Jombang.